Primary Chest Wall Abscess Mimicking a Breast Tumor That Occurred after Blunt Chest Trauma: A Case Report. (9th February 2014) - Yamaoka, Yusuke; Yamamura, Jun; Masuda, Norikazu; Yasojima, Hiroyuki; Mizutani, Makiko; Nakamori, Shoji; Kanazawa, Toru; Kuriyama, Keiko; Mano, Masayuki; Sekimoto, Mitsugu
Abstract : Primary chest wall abscess occurring after blunt chest trauma is rare. We present the case of a 50-year-old woman who presented with a swelling in her left breast. The patient had experienced blunt chest trauma 2 months back. Needle aspiration revealed pus formation in the patient's chest. Computed tomography revealed a mass in the lower region of the left mammary gland, with thickening of the parietal pleura and skin and fracture of the fifth rib under the abscess. Following antibiotic administration and irrigation of the affected region, surgical debridement was performed. During surgery, we found that the pectoralis major muscle at the level of the fifth rib was markedly damaged, although the necrotic tissue did not contact the mammary gland. We diagnosed the lesion as a chest wall abscess that occurred in response to blunt chest trauma. Her postoperative course was uneventful. There has been no recurrence for six months after surgery.